INTERACTIONS BETWEEN METAL OXIDES AND SPECIES OF NITROGEN AND IODINE IN BIOTURBATED MARINE SEDIMENTS - Anschutz P.; Sundby B.; Lefrancois L.; Luther G.W.; Mucci A. (My University, 2000)
By using a gold amalgam (Au/Hg) voltammetric microelectrode, we have measured simultaneously and with millimeter resolution the distributions of O2, Mn(II), Fe(II), I(-I), and HS(-I) in bioturbated sediment cores from the Laurentian Trough. We also measured nitrate and ammonia in the pore water, total I and ascorbate- and HCl-extractable Fe and Mn in the solid-phase sediment, and fluxes of O2, NO3-, and NH4+ across the sediment-water interface. The concentrations of O2 and Mn(II) were below their respective detection limits of 3 and 5 μM between 4 and 12 mm depth, but a sharp iodide maximum occurred at the depth where upward diffusing Mn(II) was being removed. We propose that the iodide peak is maintained through the reduction of IO3- by Mn(II), reoxidation of I(-I) to IO3- in the oxic zone above the peak and oxidation to I2 below where it is ultimately trapped by reaction with organic matter. The iodide production rate is sufficient to account for the oxidation of all of the upward diffusing Mn(II) by IO3-.Nitrate plus nitrite (ΣNO3) decreased to a minimum within 10 mm of the sediment-water interface, in agreement with flux measurements which showed ΣNO3 uptake by the sediment. Below the minimum, ΣNO3 rebounded, and reached a maximum at 40- to 50-mm depth. This rebound is attributed to the anaerobic oxidation of ammonia by manganese oxides. Fe(II) was always first detected below the anoxic ΣNO3 maximum, and was accompanied by colloidal or complexed Fe(III). A sharp upward-directed ammonia gradient was recorded near the sediment-water interface, but no ammonia was released during the first 48 h of the incubations. If the ammonia removal were due to coupled bacterial nitrification-denitrification, more than one half of the total measured oxygen uptake (6.7 to 7.3 mmol/m2/d) would be required, and more organic carbon would be oxidized by nitrate than by oxygen. This scenario is not supported by nitrate flux calculations. Alternatively, the oxidation of ammonia to N2 by manganese oxides is a potential removal mechanism. It would require one quarter of the total oxygen flux.The high-resolution profiles of redox species support the conceptualization of bioturbated sediments as a spatially and temporally changing mosaic of redox reactions. They show evidence for a multitude of reactions whose relative importance will vary over time, and for reaction pathways complementing those usually considered in diagenetic studies.